Determinant analysis of labor absorption in Maluku Province - Bin Raudha Arif Hanoeboen (Enrichment : Journal of Management, 2023)
Data from Badan Pusat Statistik (BPS) of Maluku Province shows that the absorption of labor in Maluku Province has increased quite significantly from 2019 to 2020. This research aims to analyze the effect of wage level, direct investment, and education level on employment opportunity in Maluku Province. It used panel data from BPS of Maluku Province. The results of this study indicate that wage level has a significant effect and negative relationship with employment opportunities in Maluku Province. It was indicated by probability score 0.0300 which is less than 0.05 and regression coefficient - 1.894757. Direct investment has significant effect and positive relationship to employment opportunities with probability score 0.0544 and regression coefficient 138740.1. While, education level also has significant effect and positive relationship to employment opportunities with probability score 0.0087 which is less than 0.05 and regression coefficient is 148667.3.